2016
DOI: 10.1186/s13018-016-0436-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between GDF5 +104T/C polymorphism and knee osteoarthritis in Caucasian and Asian populations: a meta-analysis based on case-control studies

Abstract: BackgroundOsteoarthritis (OA) is a degenerative joint disease with a complex genetic background. Variants in growth differentiation factor 5 (GDF5) have been reported to be associated with rheumatoid arthritis (RA) in several ethnic populations. The present study aimed to assess the association between the GDF5 +104T/C polymorphism and the susceptibility of the knee to OA through a meta-analysis of available case-control studies.MethodsThe PubMed and Science Direct citation databases were used to search electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…On the one hand, previous literatures have said that GDF 5 rs143383 polymorphisms C allele is a protective factor for the susceptibility of knee osteoarthritis among Caucasian populations (OR=0.74, P<0.001) and Asian populations (OR=0.87, P=0.004) [9]. On the other hand, Sujie Zhang et al holds that interaction GDF 5 rs143383 polymorphisms T allele increases the risk of knee osteoarthritis among Asian (OR=1.62, P<0.001) [5].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the one hand, previous literatures have said that GDF 5 rs143383 polymorphisms C allele is a protective factor for the susceptibility of knee osteoarthritis among Caucasian populations (OR=0.74, P<0.001) and Asian populations (OR=0.87, P=0.004) [9]. On the other hand, Sujie Zhang et al holds that interaction GDF 5 rs143383 polymorphisms T allele increases the risk of knee osteoarthritis among Asian (OR=1.62, P<0.001) [5].…”
Section: Discussionmentioning
confidence: 97%
“…Their limitations still remain. Firstly, Feng Pan's meta-analysis has some shortcomings, including unmatching HWE studies in their meta-analysis [9], which results are unreliable. Secondly, Xin Huang's meta-analysis explores the association between all kinds of osteoarthritis and GDF 5 rs143383 polymorphisms, which can't precisely describe the relationship between GDF 5 rs143383 polymorphisms and the susceptibility of knee osteoarthritis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although the association of the risk of knee osteoarthritis and GDF5 rs143383 genetic polymorphisms has been described in several meta-analyses [8][9][10][11][12], several recent trials also reported the risk of knee osteoarthritis and GDF5 rs143383 genetic polymorphisms [4][5][6]. On the other hand, prior meta-analyses have some limitations, such as low quality and lacking enough studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic protein-14 (BMP-14), also known as growth and differentiation factor-5 (GDF5), is one of the most frequently studied targets for OA onset. [ 10 , 11 ] Belonging to the transforming growth factor-β family, it is closely associated with BMPs, [ 12 ] and affects the development, maintenance, and repair of cartilage, bone, and other tissues of synovial joint. [ 13 17 ] BMP-14 is involved in chondrogenesis and joint formation, and mutations in its coding gene can lead to diseases, for example, chondrodysplasias.…”
Section: Introductionmentioning
confidence: 99%